Pengaruh tepung tanaman meniran terhadap aktivitas antimikroba bakteri asam laktat dan Escherichia coli - Lestariningsih Lestariningsih; Osfar Sjofjan; Edhy Sudjarwo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The study was conducted to identify the effect of meniran plant powder (Phyllanthus niruri Linn.) on microorganism activity (Lactic Acid Bacteria (LAB) and Escherichia coli). The LAB extract was put in De Man, Rogosa and Sharpe (MRS) medium and the Escherichia coli extract was put in E-Coli Medium (EM). The pure culture LAB and Escherichia coli was used to identify the effect of meniran plant powder (Phyllanthus niruri Linn.) using diffusion method. The experiment consisted of 6 treatments (P0= aquadest 100%, P1= antibiotic 100%, P2= meniran plant powder 0%, P3= meniran plant powder 50%, P4= meniran plant powder 75% and P5= meniran plant powder 100%). Variables in this research were inhibition of BAL and Escherichia coli. The study used a Nested Completely Randomized Design and if there were different effects among the treatments it would be then followed by a Duncan’s Multiple Range test. The study showed that the use of meniran plant powder (Phyllanthus niruri Linn.) had a significant effect on inhibition of BAL and Escherichia coli (P<0.01). Keywords: meniran plant, feed additive, Lactic acid bacteria and Escherichia coli